Pemanfaatan Sosial Media Tiktok sebagai Strategi Promosi dalam Berwirausaha Persfektif Ekonomi Islam - Amalia Munajah Nasution; Zuhrinal M Nawawi Elihami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The Covid19 pandemic in 2019 hampered all human activities throughout the country. Many employees were laid off and learning activities were also stopped. Everyone must also isolate in their respective homes. This makes all employees unemployed, meanwhile every human being has their own needs such as eating, doing activities, and others. Over the years the unemployment rate has skyrocketed. Meanwhile, social media, especially the tiktok application, is becoming a hot trend among young people and adults. This pandemic has made mankind rack their brains to keep meeting their needs in life. One way is to use social media as a marketing strategy. The purpose of this study is to provide an explanation regarding the use of social media tiktok as a marketing strategy in entrepreneurship in an Islamic economic perspective.